Experimental study of heat and mass transfer in solid dispersed materials during vapor-depression drying - Kolienko, A.; Shelimanova, O.; Biletskyi, D. (Energy and Automation, 2025)
The intensity of technological processes involving dispersed materials is most often limited by the speed of internal mass transfer. The vapor-depression drying method, developed by scientists of the Institute of Thermal Physics of the National Academy of Sciences of Ukraine, allows for the intensification of internal moisture transfer and thus creates the prerequisites for accelerating the drying process. The vapor-depression drying process has been considered in detail in the literature for the case of drying a capillary-porous body - sheet plaster. The purpose of this study is to consider the effect of a vapor-permeable shell on the intensification of internal mass transfer during the drying of a capillary-porous colloidal body - viscose fiber. In experimental studies, ordinary knitted shells and shells with increased density, as well as cloth and paper shells were used. The absence of a clearly defined period of constant drying speed was recorded, which indicates a low intensity of moisture transfer in the material. The highest values of the drying speed are achieved when using a single knitted shell, the lowest - when dewatering the fiber in a cloth shell. The obtained experimental data can be used to develop effective methods for controlling the drying processes of solid dispersed bodies. Key words: vapor-depression drying, solid dispersed bodies, vapor-permeable shell, drying rate